Intermittent Hypoxic Preconditioning: A Potential New Powerful Strategy for COVID-19 Rehabilitation - Cai, Ming; Chen, Xuan; Shan, Jieling; Yang, Ruoyu; Guo, Qi; Bi, Xia; Xu, Ping; Shi, Xiangrong; Chu, Lixi; Wang, Liyan (Frontiers in Pharmacology, 2021)
COVID-19 is a highly infectious respiratory virus, which can proliferate by invading the ACE2 receptor of host cells. Clinical studies have found that the virus can cause dyspnea, pneumonia and other cardiopulmonary system damage. In severe cases, it can lead to respiratory failure and even death. Although there are currently no effective drugs or vaccines for the prevention and treatment of COVID-19, the patient’s prognosis recovery can be effectively improved by ameliorating the dysfunction of the respiratory system, cardiovascular systems, and immune function. Intermittent hypoxic preconditioning (IHP) as a new non-drug treatment has been used in the clinical treatment of chronic obstructive pulmonary disease (COPD), diabetes, coronary heart disease, hypertension, and other diseases. Many clinical studies have confirmed that IHP can improve the cardiopulmonary function of patients and increase the tolerance of tissues and organs to ischemia. This article introduces the physiological and biochemical functions of IHP and sets the application plan of IHP for the prognosis and rehabilitation of COVID-19, so as to shorten the patient’s prognosis time and speed up the recovery of the disease. The aim of this narrative review is to propose possible causes and pathophysiology of COVID-19 based on the mechanisms of the oxidative stress, inflammation, and immune response, then to provide a new, safe and effective strategy for the prognosis and rehabilitation of COVID-19.